Upbringing and Personal Development - Ochilova, M. O.; Raximova, N. A. (European Journal of Life Safety and Stability (2660-9630), 2022)
Supporting concepts: The article explains the essence of the concepts of education and maturity of the individual. The problem of educating a perfect person is highlighted. It serves to form a fully mature and harmonious generation.